FROM THE HISTORY OF THE SAMARKAND AGRICULTURAL INSTITUTE (USING THE EXAMPLE OF THE YEARS OF INDEPENDENCE) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Today in the world, reforming the higher education system, introducing innovative methods in educating young people, identifying strategic directions in the education system, and integrating science and education are considered issues of state importance. In particular, during the years of independence, serious attention was paid to the development of the education system in Uzbekistan, along with the development of the political and economic sphere. Changes and innovations were carried out in higher educational institutions in accordance with the needs of the time.